Череп эласмотерия кавказского (Elasmotherium caucasicum Boriss.) из поэднеплиоценовых отложений Запорожской области - Свистун, В.И. (Вестник зоологии, 1973)
Elasmotherium caucasicum skull from the Late Pliocene deposits found in 1954 in
suburbs of the town of Bolshoy Tokmak of the Zaporozhie region is described in detail and compared with the skulls of the Middle Anthropogen Khazar E. sibiricum. The skull is found in ancient alluvial stratifications, possible analogs of the Villafrankian stage, together with remains of Archidiscodon meridionalis and Allohippus stenonis.